A Framework of Core Competencies for Effective Hotel Management in an Era of Turbulent Economic Fluctuations and Digital Transformation: The Case of Shanghai, China - Li, Yuanhang; Marneros, Stelios; Efstathiades, Andreas; Papageorgiou, George (My University, 2025)
In the context of macroeconomic recovery and accelerating digital transformation in the post-pandemic era, the hotel industry in China is undergoing profound structural changes. This research investigates the core competencies required for hotel managers to navigate these challenges. Data was collected via a quantitative survey involving a structured questionnaire, was conducted among hotel managers in Shanghai, China, resulting in 404 valid responses. Employing exploratory factor analysis using SPSS, this study identifies seven key competency dimensions encompassing 36 ranked items, including interpersonal communication, leadership, operational knowledge, human resource management, financial analysis, technology, and administrative management. The results show that economic recovery has brought new opportunities but also challenges to the hotel industry, and that managers must possess a diverse set of core competencies to adapt to the demanding new market changes. The novelty of this research lies in its empirical grounding and its focus on the intersection of digitalization and economic recovery within China’s hotel industry. It pioneers a dynamic strategic competency framework tailored to the evolving demands of the hotel industry during a period of economic volatility, providing empirical evidence and advice for optimizing the industry’s talent training systems. Simultaneously, it brings a new perspective for dealing with the recovery path for the hotel enterprises in other urban and travel destinations, aiming to promote industry sustainability and competitive advantages. Future research could extend the proposed framework by exploring its applicability across different cultural and economic contexts.
Keywords: hospitality management; strategic management; digital economy; human resource management; economic recovery; core competencies